1999
DOI: 10.1161/01.cir.100.12.1354
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Regarding the Atrial Flutter Reentrant Circuit

Abstract: Background-We studied atrial activation during induced atrial flutter in the canine sterile pericarditis model to test the hypothesis that the atrial flutter reentrant circuit includes a septal component. Methods and Results-We studied 10 episodes of induced, sustained (Ͼ5 minutes) atrial flutter in 9 dogs. In all episodes, the reentrant circuit included a septal component. In 6 episodes, there were 2 reentrant circuits, one in the right atrial free wall and the second involving the atrial septum, Bachmann's b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 25 publications
4
38
0
Order By: Relevance
“…The functional line of block initially failed to develop, presumably because of the still present effect of flunarizine. This "failure" again confirms, in yet another scenario, the importance of the development of a line of functional block between the venae cavae during atrial fibrillation in order to achieve and maintain classical, right atrial, macroreentrant AFL (19,21).…”
Section: Implications Of Initial Failure But Subsequent Success In Resupporting
confidence: 56%
See 2 more Smart Citations
“…The functional line of block initially failed to develop, presumably because of the still present effect of flunarizine. This "failure" again confirms, in yet another scenario, the importance of the development of a line of functional block between the venae cavae during atrial fibrillation in order to achieve and maintain classical, right atrial, macroreentrant AFL (19,21).…”
Section: Implications Of Initial Failure But Subsequent Success In Resupporting
confidence: 56%
“…a failed attempt to induce AFL. The key finding was absence of development of a stable line of block between the venae cavae in the right atrial free wall, the latter being required for initiation and maintenance of the AFL reentrant circuit (19,21). A stable line of block did form after completion of the pacing induction protocol prior to flunarizine administration, resulting in sustained AFL.…”
Section: Open Chest Studies: Simultaneous Multisite Atrial Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…The atrial figure-of-eight re-entry has been described in the canine sterile pericarditis model (20,21). Schoels et al (20) demonstrated that 2 of 11 dogs (4 episodes) showed double-loop re-entry during sustained AFL.…”
Section: Discussionmentioning
confidence: 99%
“…These authors using 372 unipolar electrodes arranged in 186 bipolar pairs concluded that AFL was caused by a reentrant excitation that always included a septal component, did not always require a right atrial free wall reentrant circuit and was associated with a line of functional conduction block in the right atrial free wall. 16,26) The tricuspid ring annulus was not the primary site of rotation during AFL in Waldo's model. These authors further showed that that a positive flutter wave in ECG lead II (counterclockwise circus movement) was associated with early activation of the Bachmann's bundle region compared with the posteroinferior left atrium and a negative flutter was associated with the early activation of the posteroinferior left atrium compared with Bachmann's bundle and activation of a considerable portion of the left atrium in an inferosuperior direction (clockwise circus movement).…”
Section: The Era Of Computerized Mappingmentioning
confidence: 89%